2016
DOI: 10.1080/0376835x.2015.1120656
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of small and medium enterprises in informal metal manufacturing in Zimbabwe: Implications for stakeholders in the agricultural sector

Abstract: The International Center for Tropical Agriculture (CIAT) believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture.CIAT is committed to creating and sharing knowledge and information openly and globally. We do this through collaborative research as well as through the open sharing of our data, tools, and publications. Citation:Makate, Clifton; Siziba, Shephard; Hanyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…One of the approaches widely used to conceptualize and represent the influence of enterprises and institutions on the market is based on the Theory of Industrial Economics, which seeks to adapt to the internal and external forces required by the economic relations of the market. This approach is recognized by the Structure-Conduct-Performance (SCP) Paradigm which provides data from organizations, establishing an important relation among how enterprises are being conducted within their industry, their structures and their economic performance (Makate, Siziba, Hanyani-Mlambo, Sadomba & Mango, 2016).…”
Section: Obstacles and Barriers In The Sci Processmentioning
confidence: 99%
“…One of the approaches widely used to conceptualize and represent the influence of enterprises and institutions on the market is based on the Theory of Industrial Economics, which seeks to adapt to the internal and external forces required by the economic relations of the market. This approach is recognized by the Structure-Conduct-Performance (SCP) Paradigm which provides data from organizations, establishing an important relation among how enterprises are being conducted within their industry, their structures and their economic performance (Makate, Siziba, Hanyani-Mlambo, Sadomba & Mango, 2016).…”
Section: Obstacles and Barriers In The Sci Processmentioning
confidence: 99%
“…A study by Charoenrat et al (2013) also implied that SMEs and MSMEs have a high technical inefficiency level in the production process. On the other hand, the research conducted by Ramadani & Boedirochminarni (2017) demonstrated the efficient performance of MSMEs that the government coached MSMEs inefficiencies were also found in the informal metal fabrication companies in Zimbabwe, indicating a high level of technical inefficiency in the production process (Makate et al, 2014).…”
Section: Introductionmentioning
confidence: 99%